Pulmonary Expression of TNF- Following Exposure to Mixture of Chlorpyriphos and Cypermethrin with or without Endotoxin - Nazki, Mahwash (Indian Journal of Veterinary Anatomy, 2020)
The present investigations included male albino mice (N=48) aging 6-8 weeks to evaluate the expression of TNF- α in response to chlorpyriphos, cypermethrin and their mixture with or without LPS challenge. The animals were divided into four groups viz. one control and three treatments (N=12). Treatment groups were orally administered with chlorpyriphos @2.76mg/kg, cypermethrin @2mg/kg or mixture dissolved in corn oil for 90 days followed by LPS or NSS challenge @80μl/animal via intranasal route. There was 3.95 folds (p<0.05) increase in the expression of TNF- αmRNA after administration of LPS as compared to control. Similarly, chlorpyriphos (2.70 folds), cypermethrin (2.97 folds) and their mixture (1.94 folds) resulted significant (p<0.05) increase in the expression of TNF- αmRNA compared to control. Chlorpyriphos and cypermethrin along with LPS significantly (p<0.05) increased the expression of TNF- αmRNA by 5.60 and 6.38 and 10.05 folds, respectively as compared to control, LPS and individual and combined group of chlorpyriphos or cypermethrin treated group. Immunohistochemistry results were in concurrence with mRNA expression.